Surface structure of zinc oxide ( [formula omitted]), using an atomistic, semi-infinite treatment - Whitmore, Lee; Sokol, Alexey A.; Catlow, C.Richard A. (Surface science, 2002)
The surface structure of zinc oxide (1 0 1 ̄ 0) has been investigated computationally using new atomistic potentials in an effort to rationalise results of previous experimental and theoretical studies. We find that the uppermost zinc atoms have a significant relaxation towards the bulk (0.25 Å) but the zinc atoms in the second layer show a significant relaxation away from the bulk (0.165 Å), allowing them to appear as surface atoms. In agreement with recent ab initio results, only small relaxation is found for surface oxygen atoms. Our results suggest a high and variable concentration of dimer defects in both layers one and two, where the energetic cost for defect formation is very low, which promotes the likelihood of two-layer defects, consistent with the observed two-layer step height. The bulk termination is also subject to high concentrations of dimer vacancies which corresponds to recent findings of fractional occupations in the surface layers by Jedrecy et al. [Surf. Sci. 460 (2000) 136].